An immunosuppressive therapeutic approach targeting interleukin-35 for controlling excessive immunoinflammatory response during Plasmodium berghei ANKA infection in mice - Omenesa, Ramatu Bello (2019)
Accounting for 219 million cases and 435 thousand deaths in 2017, malaria infection represents a major public health menace globally. Despite sustained efforts aimed at curbing its associated morbidity and mortality, approximately 3.2 billion individuals worldwide are at risk of contracting malaria. Malaria leaves in its wake devastating impacts on the welfare and socioeconomic stance of a nation. At present, an effective cure against malaria remains elusive. Nevertheless, greater understanding of hostparasite interactions during malaria has revealed the significant contributions of cytokines in mediating between pathology and protection. This study aimed to investigate the involvement of the recently elucidated cytokine interleukin-35 in a rodent model of malaria infection and to determine the effects of modulating the release of IL-35 on inflammatory cytokine responses, histopathological outcomes and survival of mice infected with malaria. Plasmodium berghei ANKA infection in ICR mice (N=90) was selected owing to its propensity for producing severe infections and cerebral manifestations that closely resemble human infections with Plasmodium falciparum. Infection was initiated with 0.2 mL of 2 x 107 P. berghei parasitized red blood corpuscles administered intraperitoneally. Onset and progression of malaria was assessed daily. Levels of IL-35 in systemic circulation during P. berghei infection were quantified in serum from infected and healthy mice via ELISA while tissue expression of IL-35 was characterized by immunohistochemistry. Subsequently, the impact of modulating IL-35 on the cytokine repertoire during P. berghei infection, effects on organ-specific pathological manifestations in addition to the overall course of malaria infection and survival was explored. A significant increase (p <0.0001) in serum and tissue levels of IL-35 was observed in P. berghei infected mice (n=10) compared to un-infected control mice. Serum levels of IL-35 correlated significantly with parasitaemia (r2 = 0.608, p <0.001). Recombinant IL-35 protein treatment during infection (n=10) prompted similar levels of parasitaemia, TNF-α, IFN-γ, IL-6 and elevated levels of, IL-2 (p <0.01) compared to PBS treated positive controls. Conversely, parasitemia levels in infected mice that received neutralizing anti Epstein Barr virus-induced gene 3 protein antibody (AEBI3) were greatly decreased (p <0.001) compared to rmIL-35 protein treated mice and positive control mice. Likewise, levels of IFN-γ were markedly increased (p <0.001) in addition to IL-10 and TNF-α (p <0.01) while IL-6 was significantly decreased (p <0.01) following treatment with neutralizing AEBI3 antibody. Likewise, infected mice treated with recombinant IL-35 demonstrated pathological features consistent with malaria infection and succumbed to infection beginning from the fourth day (60 %) with 100 % mortality by the sixth day of infection unlike the neutralizing AEBI3 antibody treated mice in whom there was only minimal evidence of malaria pathology and demonstrated survival advantage succumbing to infection by the ninth day of infection. Taken together, the results reveal the involvement of IL-35 in malaria infection initiated by P. berghei ANKA parasite and proffer a role for IL-35 neutralization strategies as a potential therapeutic approach beneficial for ameliorating severe malaria infection.